The Impact of Emotion on Learners' Application of Basic Science Principles to Novel Problems. (November 2016) - McConnell, Meghan M.; Monteiro, Sandra; Pottruff, Molly M.; Neville, Alan; Norman, Geoff R.; Eva, Kevin W.; Kulasegaram, Kulamakan
Abstract : Purpose: Training to become a physician is an emotionally laden experience. Research in cognitive psychology indicates that emotions can influence learning and performance, but the materials used in such research (e.g., word lists) rarely reflect the complexity of material presented in medical school. The present study examined whether emotions influence learning of basic science principles. Method: Fifty-five undergraduate psychology students were randomly assigned to write about positive, negative, or neutral life events for nine minutes. Participants were then taught three physiological concepts, each in the context of a single organ system. Testing consisted of 13 clinical cases, 7 presented with the same concept/organ system pairing used during training ("near transfer") and 6 with novel pairings ("far transfer"). Testing was repeated after one week with 13 additional cases. Results: Forty-nine students provided complete data. Higher test scores were found when the concept/organ system pairing was held constant (near transfer = 51% correct vs. far = 33%; P < .001). Emotion condition influenced participants' overall performance, with individuals in the neutral condition (50.1%) performing better than those in the positive (38.2%, P < .05) and negative (37.7%, P < .001) emotion conditions. Conclusions: These data suggest that regardless of whether the emotion is positive or negative, mild affective states can impair learning of basic science concepts by novices. Demands on working memory and subsequent cognitive load provide a potential explanation. Future work will examine the extent to which these findings generalize to medical trainees.